2011
DOI: 10.1007/8904_2011_69
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Edema in Maple Syrup Urine Disease Despite Newborn Screening Diagnosis and Early Initiation of Treatment

Abstract: A 7-day-old girl had an elevated leucine level on newborn screen drawn at 2 days of age and was suspected of having maple syrup urine disease (MSUD). When reported, the patient was immediately admitted to hospital, and started on a modified diet involving high calories with reduced branched chain amino acid (BCAA) formula. Clinical exam was normal at initial assessment. Despite rapid initiation of treatment, the baby became lethargic and somnolent over the next day. Diet was stopped and infusions of 12.5% dext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Chace et al [139] first described the use of TMS for MSUD NBS and recommended the determination of total leucine (Xle) in combination with a total leucine and phenylalanine ratio (Xle/Phe, respectively) for improved detection. In the following studies, recommendations for MSUD detection was based on an elevated Xle or leucine (Leu) [112,[140][141][142][143][144][145][146][147]. Some studies reported that Val is also required for referral [148][149][150] while others did report Val, but without the cut-off value [139,143,151].…”
Section: Figurementioning
confidence: 99%
“…Chace et al [139] first described the use of TMS for MSUD NBS and recommended the determination of total leucine (Xle) in combination with a total leucine and phenylalanine ratio (Xle/Phe, respectively) for improved detection. In the following studies, recommendations for MSUD detection was based on an elevated Xle or leucine (Leu) [112,[140][141][142][143][144][145][146][147]. Some studies reported that Val is also required for referral [148][149][150] while others did report Val, but without the cut-off value [139,143,151].…”
Section: Figurementioning
confidence: 99%
“…4 Roughly 50%-75% of MSUD patients fall into the classic MSUD phenotype, with symptomatic onset within a few days after birth including neurologic abnormalities such as dystonia, apnea, seizures, and signs of cerebral edema due to toxic accumulation of leucine and KIC in the blood and brain; if untreated, coma and death can ensue. 5,6 Elevated leucine and KIC levels in the brain appear to be the primary cause of these symptoms due to abnormal cerebral protein and neurotransmitter metabolism. 7,8 An intermediate MSUD phenotype presents later in childhood with episodes of acute metabolic decompensation or neurological symptoms and developmental delay.…”
Section: Introductionmentioning
confidence: 99%
“…10 Many patients on strict diet still fail to maintain healthy leucine levels and may experience mild to moderate neurological symptoms and developmental delay. 6 Furthermore, patients on dietary therapy may still undergo life-threatening episodes of metabolic crisis caused by catabolism of endogenous protein induced by intercurrent illness or by exercise, injury, surgery, fasting, or dietary noncompliance. 9 Patients with MSUD, as with other inborn errors of amino acid metabolism such as phenylketonuria and homocystinuria, must maintain constant dietary vigilance, and lifelong compliance is extremely challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The classic type with <2% of the normal enzyme activity exhibits the most severe phenotype. In the absence of timely diagnosis and treatment, the neonate with classic MSUD may succumb to early death due to brain edema from leucine neurotoxicity soon after birth ( Levin et al, 1993 ; Strauss et al, 2010 ; Myers et al, 2012 ). In the present study, we described a Chinese patient with the severe classic form of MSUD caused by a missense mutation and a novel large deletion mutation in the BCKDHB gene.…”
Section: Introductionmentioning
confidence: 99%